2018
DOI: 10.1111/zph.12491
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and characterization of seven major Shiga toxin‐producing Escherichia coli serotypes from healthy cattle on cow–calf operations in South Africa

Abstract: Cattle are a major reservoir of Shiga toxin-producing Escherichia coli. This study investigated the occurrence of seven major STEC serogroups including O157, O145, O103, O121, O111, O45 and O26 among 578 STEC isolates previously recovered from 559 cattle. The isolates were characterized for serotype and major virulence genes. Polymerase chain reaction revealed that 41.7% (241/578) of isolates belonged to STEC O157, O145, O103, O121, O45 and O26, and 33 distinct serotypes. The 241 isolates corresponded to 16.5%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 63 publications
2
16
1
Order By: Relevance
“…Non-O157 E. coli that possess a high proportion of stx2 to stx1 genes as documented in this study have been identified in other studies from South Africa [57], Iran [58] and the United States [59]. However, this observation is contrary to the studies conducted in Western Canada [60] and Europe [61], where non-O157 isolates have been found to harbour more stx1 - than stx2 genes.…”
Section: Discussioncontrasting
confidence: 88%
“…Non-O157 E. coli that possess a high proportion of stx2 to stx1 genes as documented in this study have been identified in other studies from South Africa [57], Iran [58] and the United States [59]. However, this observation is contrary to the studies conducted in Western Canada [60] and Europe [61], where non-O157 isolates have been found to harbour more stx1 - than stx2 genes.…”
Section: Discussioncontrasting
confidence: 88%
“…with stx virulence genes incorporated into the bacterial genome, and as free stx-encoding bacteriophage. Such high carriage by cattle has been reported in several countries, including the US, Canada, Europe, and Australia (39)(40)(41)(42)(43)(44). Across all these studies, the prevalence of stx2 is greater than that of stx1, similar to our own observations.…”
Section: Herd Risk Analysissupporting
confidence: 90%
“…Currently, STEC surveillance in South Africa remains passive and STEC disease in South Africa may be underestimated due to lack of active surveillance and/or underreporting. In addition, with cattle being an important STEC reservoir [44], the apparent sporadic nature of the disease in humans may be an inaccurate reflection of the true prevalence of STEC infection in humans. In this study, STEC isolates that were implicated in sporadic human disease in South Africa between 2006 and 2013 were characterized for virulence-associated genes and antimicrobial resistance profiles.…”
Section: Discussionmentioning
confidence: 99%
“…The eaeA gene was observed in the following serotypes: STEC O5:HNT, O26:H11, O111:H8, O118:H16, O157:H7 and ONT:H8. The high frequency of eaeA in these human STEC isolates is in sharp contrast with the very low rates of eaeA found in STEC isolates from cattle in South Africa [44], which are considered an important STEC reservoir, suggesting that only a small subset of cattle STEC that are eaeA positive with a high capacity of being easily transmitted to humans may be involved in human disease in South Africa.…”
Section: Discussionmentioning
confidence: 99%